The Value of Islamic Education in the Megengan Tradition at Kaliaren Village - Wardhani, Ayu Era (Lembaga Yasin AlSys, 2023)
Religious traditions in Java are wrapped with interesting Javanese culture without losing the Islamic values, such as Megengan tradition which is carried out at the end of the month of Sya'ban (Ruwah) before the arrival of the month of Ramadhan. This tradition is also carried out by the community of Rt 01 Rw 03 Sendang Village, Donorojo, Pacitan, East Java. Megengan tradition is interesting to study, because in today's modern era when changes and developments in science are increasingly advanced, the Megengan tradition is still firmly held and still on going. The type of research used is a qualitative research approach, the primary data sources used are observations, interviews with religious figures, village heads and local communities. Some documentation in the form of photos as secondary data sources were also obtained to strengthen the research. Data collection techniques were carried out by interviews, observation, and documentation. While analyzed by means of Data Reduction, Data Presentation and Drawing Conclusions. The values of Islamic education contained in the Megengan tradition carried out by the people of Rt 01 Rw 03 Sendang as a form of gratitude to Allah Swt for all the blessings that have been given, pray together for the family who has died, and establish ukhuwah Islamiyah between communities. This is done with the foundation of togetherness in social life to strengthen friendship. The Megengan tradition explains how religious traditions are wrapped in traditional Javanese cultural patterns, and do not come out of Islamic law with the Qur'an and Hadith as the foundation.